The binding : a novel - Collins, Bridget (William Morrow, an imprint of HarperCollinsPublishers, 2019)
"In the tradition of Sarah Waters, Helene Wecker, and Jessie Burton, an atmospheric and mystery-laden historical novel set within a magical world where books are not stories but the repository of individual lives"--